The association between first and second wave COVID-19 mortality in Italy - Marco Vinceti; Tommaso Filippini; Kenneth J. Rothman; Silvia Di Federico; Nicola Orsini (BMC, 2021)
Abstract Background The relation between the magnitude of successive waves of the COVID-19 outbreak within the same communities could be useful in predicting the scope of new outbreaks. Methods We investigated the extent to which COVID-19 mortality in Italy during the second wave was related to first wave mortality within the same provinces. We compared data on province-specific COVID-19 2020 mortality in two time periods, corresponding to the first wave (February 24-June 30, 2020) and to the second wave (September 1-December 31, 2020), using cubic spline regression. Results For provinces with the lowest crude mortality rate in the first wave (February-June), i.e. < 22 cases/100,000/month, mortality in the second wave (September-December) was positively associated with mortality during the first wave. In provinces with mortality greater than 22/100,000/month during the first wave, higher mortality in the first wave was associated with a lower second wave mortality. Results were similar when the analysis was censored at October 2020, before the implementation of region-specific measures against the outbreak. Neither vaccination nor variant spread had any role during the study period. Conclusions These findings indicate that provinces with the most severe initial COVID-19 outbreaks, as assessed through mortality data, faced milder second waves.